Delabelling beta-lactam allergy - Molina-Molina, Gustavo-Jorge; Garnica Velandia, Diana Rocío; Andrés-López, Blanca; Perales, Carolina; Marin-Asensio, Laura; Jurgens, Yanina; Esteso, Olga; Escobar, Carolina; Vidal, Xavier; Vendrell, Lourdes; Gómez-Ganda, Laura; Rodríguez, Dolores; et al. (Frontiers in Pharmacology, 2024)
Hypersensitivity to beta-lactam (BL) antibiotics is one of the most frequent reported drug allergy. In our population it is frequent to find labels of BL allergy in electronic medical records (EMR) that have not been assessed.Our objective was to detect patients with BL allergy label in their EMR and to assess how many of them are false after a correct diagnostic evaluation.A multicentre prospective study was performed with patients labelled as allergic to BLs in their EMR in the previous five years. Demographical, clinical data as well as variables regarding the BL allergy Formatat: Espanyol (Espanya) Formatat: anglès (EUA) Formatat: anglès (EUA)